Designe and Development of Ardrino based Digital RPM Meter - Das, S; Nandy, R (International Journal of Computer Sciences and Engineering, 2025)
Contact less Digital RPM meter is a device used to measure speed of a rotating body by counting the number of rotations per second of a rotating shaft using Arduino as the main controller along with the IR sensor with bluetooth connectivity to send the measured value of RPM to some remotely located receiver. It works on the principle of The IR sensor kept in front of a rotating body within a specified range of measurement. The number of counts from the IR sensar signal cut by the rotating body introduce the sense of RPM value which is displayed on the LCD display. The Arduino nano(ATmega 328P) is used as a microcontroller along with IRS sensar (MH-sensar-series, MH-B) and Bluetooth device (HC-05) are the main constituing parts of this measuring system. The designed system is unique from the conventional tachometers as the RPM measurement is not only contactless but it can also be transmitted to some remotely located control room for recording, processing and analysis of the rotating system parameters.